Preliminary Phase of the Right of Assessment in Iran and France with Emphasis on One Article to Respect Legal Freedom and Protection of Citizenship Rights - Emadoleslami, Zahra; Ghorbani, Hadi (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2019)
Abstract The right of citizenship in criminal law is one of the important cases in the field of human rights and has received attention from various human rights documents. In Iran's criminal law in various cases also respect to legal freedom and protection of citizenship rights. Besides trying to give more attention to citizenship rights based on fair assessment. An important question that can be raised in is howthe regulation to respect the legal freedom and protection of citizenship rights in Iranian law proportional to French law in terms of a fair assessment? The findings from this survey show that there is a compilation of regulation respecting legal freedom and protecting citizenship rights. In addition, there is an internalization effort to pay attention the human rights in criminal justice, in the form of action to eliminate the aggression against the rights of citizen and this rule emphasizes cases that consistent with French law. In the rules of respect for legal freedom and protection of citizenship rights, such as the rights of convicted people in France, it has emphasized the existence of freedom, personal security, prohibition of torture, self-respect of the accused by defending their rights and protecting themselves.Keywords: Freedom of law, human rights, citizenship rights, fair assessment, Iranian law, French law AbstrakHak kewarganegaraan dalam hukum pidana adalah salah satu kasus penting di bidang hak asasi manusia dan telah mendapatkan perhatian dari berbagai dokumen hak asasi manusia. Dalam hukum pidana Iran dalam berbagai kasus juga memberikan penghormatan terhadap kebebasan hukum dan perlindungan hak kewarganegaraan. Selain diupayakan untuk memberikan perhatian lebih terhadap hak kewarganegaraan berdasarkan penilaian yang adil. Pertanyaan pentingdalam hal ini adalah seberapa besar aturan penghormatan terhadap kebebasan hukum dan perlindungan hak kewarganegaraan dalam hukum Iran berbanding lurus dengan hukum Prancis dalam sudut pandang penilaian yang adil? Temuan-temuan dari survey ini menunjukkan bahwa adanya kompilasi aturan penghormatan terhadap kebebasan hukum dan perlindungan hak kewarganegaraan. Selain itu, adanya upaya internalisasi untuk memberikan perhatian terhadap hak asasi manusia dalam peradilan pidana, berupa tindakan untuk menghapus tindakan agresi terhadap hak-hak warga negara, dan aturan ini menekankan pada kasus-kasus yang relevan dengan hukum Prancis. Dalam aturan penghormatan terhadap kebebasan hukum dan perlindungan hak-hak kewarganegaraan, seperti hak-hak terpidana di Perancistelah ditekankan pada adanya kebebasan, keamanan pribadi, larangan penyiksaan, penghargaan diri orang yang tertuduh dengan membela hak-hak dan melindungi diri pribadi.Kata kunci: Kebebasan hukum, hak asasi manusia dan hak kewarganegaraan АннотацияПраво на гражданство в уголовном праве является одним из самых важных в области прав человека и привлекает внимание в различных документах по правам человека. В Иране уголовное право в различных случаях также уважает правовую свободу и сохранение гражданских прав и стремится уделять больше внимания гражданским правам на основе справедливого суждения. Важный вопрос, который может быть поднят в этом отношении, заключается в том, насколько правило уважения к правовой свободе и сохранению гражданских прав в иранском законодательстве прямопропорционально французскому законодательству с точки зрения справедливого суждения. Результаты этого исследования показывают, что существует свод правил, которые уважают правовую свободу и сохранение гражданских прав. Кроме того, предпринимаются усилия по интернализации, направленные на то, чтобы уделять внимание правам человека в сфере уголовного правосудия в форме ликвидации действий агрессии против гражданских прав. Данное положение подчеркивает случаи, которые соответствуют французскому законодательству. В правилах уважения правовой свободы и сохранения гражданских прав, таких как права осужденных во Франции, подчеркивается существование свободы, личной безопасности, запрета пыток, самооценки обвиняемого путем защиты их прав и себя. Ключевые слова: правовая свобода, права человека, гражданские права, справедливое суждение, иранское право, французское право